From heartbeat to data—using wearable fitness trackers as an affordable approach to assess teachers’ stress - Klatt, Mandy; Lotz, Christin; Keßler, Peer; Kachel, Gregor; Deiglmayr, Anne (Frontiers in Education, 2025)
IntroductionPast research on physiological indicators of teacher stress often had to rely on expensive and obtrusive assessment methods. Modern fitness trackers represent a non-invasive and convenient alternative.MethodsThis study investigated the use of wrist-worn fitness trackers to assess teachers’ heart rate (HR) as an indicator of stress during teaching. In a laboratory study, we used a Fitbit® fitness tracker to assess teachers’ HR before, during, and after a potentially stressful micro-teaching unit.ResultsOur results demonstrated that the fitness tracker was useful for mapping teachers’ stress, with the data showing how teachers’ HR increased before, peaked during, and progressively decreased after the micro-teaching unit. Moreover, we related the fitness tracker data to retrospective teacher self-reports and found that teachers’ subjective stress appraisals and their teaching experience explained only small amounts of variance in HR data.DiscussionWe discuss the potential of fitness trackers as an affordable and ubiquitous assessment tool for research on teacher stress in the classroom and provide advice for practical implementation.